2003
DOI: 10.1110/ps.0232003
|View full text |Cite
|
Sign up to set email alerts
|

Low free energy cost of very long loop insertions in proteins

Abstract: Long insertions into a loop of a folded host protein are expected to have destabilizing effects because of the entropic cost associated with loop closure unless the inserted sequence adopts a folded structure with aminoand carboxy-termini in close proximity. A loop entropy reduction screen based on this concept was used in an attempt to retrieve folded sequences from random sequence libraries. A library of long random sequences was inserted into a loop of the SH2 domain, displayed on the surface of M13 phage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 19 publications
3
61
0
Order By: Relevance
“…Previous studies conducted on flexible loop regions revealed that the energetic consequences of changing loop length are predominantly related to the entropic cost of ordering a loop upon folding (18)(19)(20)(21)(22). This effect can be approximated by simple polymer models of the form…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted on flexible loop regions revealed that the energetic consequences of changing loop length are predominantly related to the entropic cost of ordering a loop upon folding (18)(19)(20)(21)(22). This effect can be approximated by simple polymer models of the form…”
Section: Resultsmentioning
confidence: 99%
“…Fast loop closure on the nanosecond time scale has been reported (Lapidus et al 2000;Buscaglia et al 2003;Krieger et al 2003). Concerns about the entropy cost of loop closure can be considered in the context of (1) a study of the probability of loop closure showing less than a one order of magnitude change of the probability between 10 and 40 residue chain segments (Camacho and Thirumalai 1995); (2) several studies showing that the entropy cost is low (Scalley- Kim et al 2003;Wang et al 2005). One reason that the entropy change is expected to be balanced by the NLIs is that only the loop ends are constrained, while the rest of the chain between them is free to occupy a large number of conformations under the constraints of the chain collapse.…”
Section: The Loop Hypothesismentioning
confidence: 99%
“…PEG linked to PLGA not only significantly improves the hydrophilicity of PLGA but also greatly prolongs the cycle of drugs in the body. 20 Also, PEG has good solubility in water and high solubility in most organic solvents. These features make it easier to react with PLGA in organic solvent, which greatly reduces the difficulty of the reaction.…”
Section: Introductionmentioning
confidence: 99%